Common littoral pycnogonids of the Mediterranean Sea - Tobias Lehmann; Martin Heß; Roland Melzer (Zoosystematics and Evolution, 2014)
In the present study 21 littoral pycnogonid species from 5 families are analysed: Ammotheidae (9 species), Callipallenidae (5 species), Endeidae (2 species), Phoxichilidiidae (3 species), and Pycnogonidae (2 species). The material was mainly taken from Mediterranean pycnogonid collections housed in the Bavarian State Collection of Zoology. Additional material was collected during field trips. Altogether the material was obtained from six different locations: Banyuls-sur-Mer (France), Tavolara Island (Italy), Elba Island (Italy), Giglio Island (Italy), Sicily Island (Italy), and Istria Peninsula (Croatia). The animals were studied in detail with a scanning electron microscope (SEM). Additionally series of light microscopic pictures were made to generate extended depth of field pictures of whole animals. The observed features are compared with previous literature.